Collective action problems and direct democracy: An analysis of Georgia's 2010 trauma care funding amendment - Joshua C. Hall; Jeremy Horpedahl; E. Frank Stephenson (Economies, 2021)
In 2010, Georgians voted on a proposed constitutional amendment that would have increased motor vehicle licensing fees by USD 10 with the proceeds dedicated to maintaining and expanding the state's trauma care centers. This paper examines voter support for the referendum across counties and finds (1) that counties located near trauma centers in neighboring states had significantly lower support for the amendment and (2) that counties already having trauma centers had higher support for the amendment. These results are, respectively, consistent with free-riding and rent-seeking on the part of voters.
Keywords: D72; H75; I18; 330; free-riding; referendum; rent seeking; trauma center